THE INTERNATIONAL ORGANIZATION FOR MIGRATION AS A SUBJECT ENSURING THE ADMINISTRATIVE LEGAL PERSONALITY OF MIGRANTS - Strelnykov, Andrii V.; Стрельников, Андрій Вікторович; Стрельников, А. В. (Національний університет "Одеська юридична академія"; Юридика, 2023)
The system of subjects ensuring the administrative legal personality of migrants encompasses not only state (state bodies, state enterprises, and institutions) but also non-state (local self-government) institutions. At the same time, law enforcement practice indicates that the quantity of such subjects changes dynamically, which is determined by the need to solve many issues in implementing the state migration policy. Currently, in the field of ensuring the administrative legal personality of migrants, international organizations are gaining importance, which will provide the rights and freedoms of migrants, adhering to international standards and requirements.
Strelnykov A. V. The international organization for migration as a subject ensuring the administrative legal personality of migrants // Європейські орієнтири розвитку України в умовах війни та глобальних викликів ХХІ століття: синергія наукових, освітніхта технологічних рішень : у 2 т. : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 19 травня 2023 р.) / за заг.ред. С. В. Ківалова. – Одеса : Видавництво «Юридика», 2023. –Т. 2. – С. 33-35.
Keywords: legal personality; administrative legal personality; migrant, international organization; International Organization for Migration; правосуб’єктність; адміністративна правосуб’єктність; мігрант; міжнародна організація; Міжнародна організація з питань міграції; Research Subject Categories::LAW/JURISPRUDENCE